Three Dimensional MHD Ferrous Nanofluid Flow Over a Sheet of Variable Thickness in Slip Flow Regime. (April 2019) - Kumar, R.; Raju, C. S. K.; Sekhar, K. R.; Reddy, G. V.
ABSTRACT: In the present paper, we analyzed the effects of magnetic field on the three dimensional flow of a nanofluid having the suspension of ferrous nano-particles within the framework of a non-uniformly thicked sheet in a slip flow regime. The sheet of variable thickness is assumed to be stretched in horizontal and transverse directions. The effects of thermophoretic forces and Brownian motion have also been incorporated into the governing equations. The RK-Fehlberg-integration scheme with shooting technique is employed to resolve the altered governing non-linear differential equations. Velocity, temperature and concentration profiles are presented and discussed for two cases namely uniform thickness stretching sheet UTSS (n = 1) and variable thickness stretching sheet VTSS (n ≠ 1), and skin friction coefficient, reduced Nusselt number and Sherwood number are computed and analyzed through tables. The results reveal that heat and mass transfer processes over slendering sheet matches with those over a flat sheet in the presence of slip flow regime.